Perceived Containment as a Predictor of Children’s Aggression Towards Peers - Kristina L Gowin (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
The current study investigates the extent to which children’s levels of perceived containment predict their aggression towards peers in a community program in a sample of 132 school-age children (Mean age = 8.83 years; 55% male). Perceived Containment was assessed by the administration of the Perceived Containment Questionnaire (PCQ) (Schneider et al., 2003). Relational Aggression was measured by using the Children’s Social Behavior Scale-Teacher Report (Crick et al., 1996). Children’s ratings on the Perceived Containment Questionnaire were found to be unrelated to staff reports of relational aggression. However, a direct relationship was discovered between children's ratings on the Perceived Containment Questionnaire and staff reports of physical aggression. These findings suggest that perceived containment may be a predictor of children’s physical aggression towards peers and this relationship is deserving of further investigation.
Keywords: Aggression; Children; Social Behavior